Ripple compensation for a class-D amplifier - Cox, Stephen M.; du Toit Mouton, Hendrik (SIAM, 2015)
This paper presents the first detailed mathematical analysis of the ripple compensation technique for reducing audio distortion in a class-D amplifier with negative feedback. The amplifier converts a relatively low-frequency audio signal to a high-frequency train of rectangular pulses whose widths are slowly modulated according to the audio signal (pulse-width modulation, PWM). Distortion manifests itself through unwanted audio-frequency harmonics that arise in the output due to nonlinearities inherent in the design. In this paper, we first develop a small-signal model, which describes the fate of small-amplitude perturbations to a constant input, and demonstrate how this traditional engineering tool may be extended to allow one to infer the most significant contributions to the full output in response to a general audio input. We then compute the audio output of the amplifier through a perturbation expansion based on the ratio between audio and switching frequencies. Our results explicitly demonstrate how the ripple compensation technique significantly linearizes the output, thereby reducing the distortion.